Atypical Presentation of Testicular Adrenal Rest Tumor (TART) Leading to Bilateral Partial Orchiectomy in a 31-Year-Old Adult Revealing Primary Adrenal Insufficiency with CYP11A1 Deficiency. (23rd December 2021) - Garcia, Cyril; Dusaud, Marie; Chiron, Paul; Sollier, Mathilde; Nassouri, Sika; Groussin, Lionel; Sibony, Mathilde; Goursaud, Claire; Roucher-Boulez, Florence; Bordier, Lyse
Abstract : Adrenogenital syndrome is commonly associated with a deficiency in 21-hydroxylase but can be present in other rare enzymatic blocks. We report here the case of a 31-year-old man who presented with bilateral painful testicle lesions leading to bilateral partial orchiectomy as they were suspected for malignancy. These lesions were finally identified as benign testicle adrenal rest tumors (TARTs), and the patient was actually belatedly diagnosed with primary adrenal insufficiency due to 2 mutations of the CYP11A1 gene encoding the cholesterol side-chain cleavage enzyme (P450scc); the mutations were 940G > A (p.Glu314Lys) and c.1393C > T (p.Arg465Trp). The same mutations were found in his 29-year-old sister, who was then also diagnosed for primary adrenal insufficiency. Deficiency in P450scc is an extremely rare genetic autosomal recessive disorder with around 40 described families in the literature and 30 different mutations. As the diagnosis of delayed onset of P450Scc mutation is difficult, this case illustrates the need for a systematic endocrinological assessment in any case of bilateral testicle lesions, thus avoiding unnecessary surgery.